2021
DOI: 10.1182/blood-2021-152167
|View full text |Cite
|
Sign up to set email alerts
|

Sudden or Cardiac Deaths on Ibrutinib-Based Therapy Were Associated with a Prior History of Hypertension or Cardiac Disease and the Use of ACE-Inhibitors at Study Entry: Analysis from the Phase III NCRI FLAIR Trial

Abstract: Introduction: Ibrutinib (Ibr) is the first approved irreversible BTK inhibitor. Cardiovascular (CV) adverse events, include hypertension (HT) and atrial fibrillation (AF). Ventricular tachyarrhythmias and sudden death have been reported possibly due to off target kinase inhibition. Several randomised Phase III trials have reported low numbers of cardiac deaths, sudden/unexplained deaths, and/or ventricular arrhythmias with Ibr including 9 deaths in RESONATE-2 Trial, 11 unexplained or unwitnessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…Recently, analyses of fatal cardiac events evaluated the impact of cardiovascular disease or angiotensin-converting enzyme inhibitor use in patients treated with ibrutinib plus rituximab in the FLAIR study. 22 By contrast, the safety profile of ibrutinib has now been well established with up to 8 years of follow-up, and although use of agents acting on the renin-angiotensin system (angiotensin-converting enzyme inhibitors or angiotensin II receptor antagonists) was frequent (56%) in ibrutinib-treated patients on RESONATE-2, the incidence of cardiac events was consistent with previous reports. 23,24 Furthermore, more than half of patients in this study received medications for acid-related disorders while on study treatment, including proton pump inhibitors, with no apparent impact on PFS in ibrutinib-treated patients.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, analyses of fatal cardiac events evaluated the impact of cardiovascular disease or angiotensin-converting enzyme inhibitor use in patients treated with ibrutinib plus rituximab in the FLAIR study. 22 By contrast, the safety profile of ibrutinib has now been well established with up to 8 years of follow-up, and although use of agents acting on the renin-angiotensin system (angiotensin-converting enzyme inhibitors or angiotensin II receptor antagonists) was frequent (56%) in ibrutinib-treated patients on RESONATE-2, the incidence of cardiac events was consistent with previous reports. 23,24 Furthermore, more than half of patients in this study received medications for acid-related disorders while on study treatment, including proton pump inhibitors, with no apparent impact on PFS in ibrutinib-treated patients.…”
Section: Discussionsupporting
confidence: 86%
“… 32 However, caution is still warranted when using ACEis, especially because Munir et al found that prior use of an ACEi was correlated with a risk of sudden or cardiac death in patients receiving ibrutinib and rituximab during the phase 3 FLAIR trial (relative risk, 50.2; 95% CI, 6.3-399; P < .0001). 33 …”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular complications are important BTKi-related adverse events, including hypertension, atrial fibrillation (AF)/flutter, and importantly both ventricular arrhythmias and risk of sudden death, see Table 2 . Most afflicted patients have baseline risk factors or AF, pre-existing hypertension, or related disorders [ 44 , 49 ]. Significantly increased (approximately eightfold compared with age-matched population) [ 50 ] but low absolute incidence (approximately 1/100–300) [ 49 , 51 ] of sudden death, presumed largely from ventricular arrhythmia, are common features of studies using Ib [ 2 , 34 , 44 , 45 , 52 , 53 ].…”
Section: When Using a Btki Which Is The Preferred Agent?mentioning
confidence: 99%
“…Most afflicted patients have baseline risk factors or AF, pre-existing hypertension, or related disorders [ 44 , 49 ]. Significantly increased (approximately eightfold compared with age-matched population) [ 50 ] but low absolute incidence (approximately 1/100–300) [ 49 , 51 ] of sudden death, presumed largely from ventricular arrhythmia, are common features of studies using Ib [ 2 , 34 , 44 , 45 , 52 , 53 ]. Although one retrospective single-center study suggested that acalabrutinib is similarly associated with increased incidence of ventricular arrythmias compared with the general population, the significance of the arrythmias (largely PVCs) described is unclear and no clear association with sudden cardiac death was established from these data [ 54 ].…”
Section: When Using a Btki Which Is The Preferred Agent?mentioning
confidence: 99%